Mapping the O‐glycoproteome using site‐specific extraction of O‐linked glycopeptides (EXoO). Issue 11 (20th November 2018) - Yang, Weiming; Ao, Minghui; Hu, Yingwei; Li, Qing Kay; Zhang, Hui
Abstract: Protein glycosylation is one of the most abundant post‐translational modifications. However, detailed analysis of O‐linked glycosylation, a major type of protein glycosylation, has been severely impeded by the scarcity of suitable methodologies. Here, a chemoenzymatic method is introduced for the site‐specific extraction of O‐linked glycopeptides (EXoO), which enabled the mapping of over 3, 000 O‐linked glycosylation sites and definition of their glycans on over 1, 000 proteins in human kidney tissues, T cells, and serum. This large‐scale localization of O‐linked glycosylation sites demonstrated that EXoO is an effective method for defining the site‐specific O‐linked glycoproteome in different types of sample. Detailed structural analysis of the sites identified revealed conserved motifs and topological orientations facing extracellular space, the cell surface, the lumen of the Golgi, and the endoplasmic reticulum (ER). EXoO was also able to reveal significant differences in the O‐linked glycoproteome of tumor and normal kidney tissues pointing to its broader use in clinical diagnostics and therapeutics. Synopsis: A new method (ExoO) is introduced to define site‐specific glycans for over 3, 000 O‐linked glycosylation sites. It reveals conserved and new biology regarding the O‐linked glycoproteome and shows differential expression of O‐linked glycoproteins between human kidney and normal tissues. EXoO enables a large‐scale identification of O‐linked glycosylation sites and definition of their site‐specific glycans from complex samples. Over 3, 000 O‐linked glycosylation sites and their site‐specific glycans from over 1, 000 glycoproteins are mapped using EXoO in this study. EXoO is advantageous for locating O‐linked glycosylation sites and defining site‐specific glycans in mucin‐type glycoproteins. EXoO reveals expression differences in the O‐linked glycoproteome of tumor and normal kidney tissues. Abstract : A new method (ExoO) is introduced to define site‐specific glycans for over 3, 000 O‐linked glycosylation sites. It reveals conserved and new biology regarding the O‐linked glycoproteome and shows differential expression of O‐linked glycoproteins between human kidney and normal tissues.